1998
DOI: 10.1152/ajpendo.1998.274.5.e817
|View full text |Cite
|
Sign up to set email alerts
|

Human kidney and liver gluconeogenesis: evidence for organ substrate selectivity

Abstract: To assess the contribution of the human kidney to gluconeogenesis (GN) and its role in conversion of glutamine and alanine to glucose, we used a combination of isotopic and organ balance techniques in nine normal postabsorptive volunteers and measured both overall and renal incorporation of these precursors into glucose before and after infusion of epinephrine. In the postabsorptive basal state, renal incorporation of glutamine (27 ± 2 μmol/min) and alanine (2.1 ± 0.5 μmol/min) into glucose accounted for 72.8 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
118
0
5

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(133 citation statements)
references
References 46 publications
10
118
0
5
Order By: Relevance
“…These hormones might influence hyperglycemia during the AH, though the reports that investigated these hormones during the AH did not elucidate the mechanism of such effect. Other studies suggested that epinephrine and hypoglycemia stimulate renal glucose production [7][8][9]. Epinephrine increased during the AH in our case as well.…”
Section: Discussionsupporting
confidence: 79%
“…These hormones might influence hyperglycemia during the AH, though the reports that investigated these hormones during the AH did not elucidate the mechanism of such effect. Other studies suggested that epinephrine and hypoglycemia stimulate renal glucose production [7][8][9]. Epinephrine increased during the AH in our case as well.…”
Section: Discussionsupporting
confidence: 79%
“…The renal contribution to endogenous glucose production has been a matter of much controversy [4][5][6][7][8][9][10][11][12]28]. Much of the confusion in all likelihood has arisen from the fact that measurements across the renal bed, because of the high renal blood flow of around 1 l/min, are highly susceptible to methodological imprecision as regards analysis of differences in arteriovenous glucose concentrations and dilution of tracers.…”
Section: Discussionmentioning
confidence: 99%
“…This renewed interest in the metabolic role of the kidney was fuelled by a study by Cersosimo et al [5] who used arteriovenous balance and isotopic dilution techniques to report that in postabsorptive dogs renal glucose utilisation and production each accounted for close to 30% of total glucose turnover in the presence of net balances close to zero. More recent studies in humans have reported that the renal contribution to postabsorptive whole-body glucose production may amount to between 15 and 30%, that glutamine appears to be an important precursor for renal gluconeogenesis and that renal glucose production increases in response to epinephrine and hypoglycaemia and decreases during insulin exposure [6][7][8][9][10][11]. Other investigators, however, have failed to show any significant renal contribution to overall endogenous glucose production [12].…”
Section: Introductionmentioning
confidence: 99%
“…The kidney has a substantial capacity for gluconeogenesis, and glutamine is a major substrate for this pathway (37,38). Although the human kidney is not a net gluconeogenic organ in the postabsorptive state (39 -41), recent studies that used a combination of isotopic and mass balance techniques have provided evidence that the neutral kidney glucose exchange observed in the postabsorptive state is the result of substantial ongoing uptake and release of glucose (42,43). However, in several settings the human kidney has been shown to significantly contribute to maintaining blood glucose levels.…”
Section: Discussionmentioning
confidence: 99%
“…A shift in kidney gluconeogenetic substrates is likely to occur during acidosis because the uptake of lactate observed in subjects with normal acid-base balance is no longer evident in acidotic subjects. On the basis of carbon composition (glutamine has five carbons, glucose six) and on a complete efficiency of the gluconeogenic pathway, it is estimated that 1.2 mol of glutamine are needed to contribute to each mole of de novo synthesized glucose (43). Therefore, the net uptake of glutamine observed in acidotic subjects could account for as much as 60% of the glucose released by the kidney.…”
Section: Discussionmentioning
confidence: 99%